Identification of High and Low Branched-Chain Fatty Acid–Producing Phenotypes in Holstein Cows following High-Forage and Low-Forage Diets in a Crossover Designed Trial. Issue 2 (28th January 2022) - Picklo, Matthew J; Kalscheur, Kenneth F; Magnuson, Andrew; Bukowski, Michael R; Harnly, James; Fukagawa, Naomi K; Finley, John W
ABSTRACT: Background: Branched-chain fatty acids (BCFAs) are rumen-derived fatty acids comprising ∼2% of bovine-milk fatty acids. BCFAs possess anti-inflammatory properties and enriching the BCFA content of bovine milk may provide human health benefits. Objective: We determined whether forage content impacts the BCFA content of milk from Holstein cows and identified fatty acid phenotypes in high vs. low BCFA–containing milks. Methods: Holstein cows ( n = 62), fed for 67 d in a crossover design, consumed a diet with high forage and low concentrate (HF:C) and a diet with low forage and high concentrate (LF:C). Milk samples were collected at the end of each treatment period and fatty acid content determined. Paired t-tests, 1-factor ANOVA, sparse partial least-squares discriminant analysis (sPLSDA), and Pearson's correlation analysis were used to analyze the data. Results: The total milk fatty acid concentration for cows fed the HF:C diet was greater than that of cows fed the LF:C diet (4.2 ± 0.7 g/100 mL vs. 3.9 ± 0.9 g/100 mL). sPLSDA demonstrated separation of the dietary treatments, with BCFAs and odd-chain fatty acids as primary determinants. Total BCFA content in milk fat was elevated by HF:C intake compared with LF:C intake (1.80 vs. 1.68%). Quintile separation of high vs. low BCFA milks resulted in 4 groups: HF:C /low BCFAs, HF:C /high BCFAs; LF:C /low BCFAs, and LF:C /high BCFAs. Milks from the high BCFA quintiles had lower palmitic acid content (29.6% vs. 34.4%) but higher oleic acid content than milks from the low BCFA quintiles (19.7% vs. 17.0%). Some cows were identified as high BCFA producers or low BCFA producers regardless of diet. Conclusions: BCFA content of milk is diet-sensitive but variation in responses exists. The potential to produce milk with high BCFA content and lower SFA content needs further study. Abstract : Branched-chain fatty acid (BCFA) content of milk from Holstein cows is diet-sensitive but modified by other factors. BCFA content is negatively associated with palmitic acid content in milk fat.